Corona in Lateinamerika - Dietz, Kristina; Peters, Stefan; Schnepel, Christina (Studien zu Lateinamerika, 2022)
The coronavirus pandemic has hit Latin America particularly hard. In no other region of the world have so many people been infected with the virus as here. Influenced by the pandemic, poverty and inequality have increased, the economic crisis has worsened and, in some countries, authoritarian and repressive tendencies have grown, all of which poses enormous challenges for the region. This anthology is dedicated to the consequences of the coronavirus pandemic and pandemic policies in Latin America and the Caribbean. The articles it contains examine the consequences of the pandemic in terms of social inequalities, gender relations, violence against women, democracy, human rights, labour, the mobilisation of protest and environmental policy. They discuss what social and political lessons can be drawn from the pandemic experience in Latin America at the end of 2021, when the region is far from a post-pandemic era. With contributions by Carolina Alves Vestena, Hans-Jürgen Burchardt, Alba Carosio, Kristina Dietz, Patrick Eser, Caroline Kim, Moritz Krawinckel, Stefan Peters, Axel Rojas, Christiane Schulte, Jürgen Weller, Andréa Zhouri and Claudia Zilla.